DEVELOPMENT OF ENTREPRENEURIAL PROFESSIONAL SKILLS AMONG YOUNG PEOPLE, ESPECIALLY WOMEN SOCIO-PHILOSOPHICAL CHARACTERISTICS - G‘anyieva Malikaxon Sodiqjonovna; Shaxobiddinova Sevara (Journal Park Publishing, 2023)
In this article, from a scientific and philosophical point of view, the relevance of such an issue as the formation and development of entrepreneurial professional skills in the minds and thinking of young people and women of our society is revealed. Entrepreneurial skills are justified by the need for a new approach to changing the worldview of an individual (youth and women) at a new stage in the development of our society.
Keywords: society, personality, profession, competence, youth, women, poverty, progress, employment, lifestyle.